Provision of Psychoeducation on Decreasing Family Anxiety Triggered among Patients with Schizophrenia Relapse: A Case Report - Ellya Fadllah Samiun; Herni Susanti; Ice Yulia Wardani (International Journal of Nursing and Health Services (IJNHS), 2021)
Schizophrenia is one of the serious mental disorders that requires long-term care and medication. Clients with schizophrenia have a relapse period. When a relapse occurs, they require inpatient services at the hospital. A relapse of clients with schizophrenia triggers physical and psychological fatigue, anxiety, and frustration; the sources of stressors which can disrupt the balance of the family system. The study aimed to explore the family psycho-education to decrease the anxiety triggered among family. The results of the nursing intervention found unveiled to decrease the signs and symptoms of anxiety experienced by families. The findings also showed the increasing knowledge and ability of the family members in taking caring of clients with schizophrenia. This study recommended to provide psycho-education as part of comprehensive nursing care for schizophrenia patients and their families